2020
DOI: 10.33096/atestasi.v3i1.387
|View full text |Cite
|
Sign up to set email alerts
|

Determination Disclosure of Corporate Social Responsibility

Abstract: Corporate social responsibility is a company's commitment to contribute to sustainable economic development. This study aims to examine and discuss the effect of profitability, leverage, size of the company, the audit committee, board of directors, institutional ownership and public ownership on the disclosure of corporate social responsibility. The study population was the company went public in Indonesia and the sample is manufacturing companies listed on the Stock Exchange in 2015-2018. This research data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…Based on these signals, it can be concluded that the level of CSR disclosure policy will be carried out by the company. In their study, Winarto & Rachmawati (2020) stated that profitability does not affect CSR disclosure. It shows that although the company has a high profit-in other words, it has a lot of money to do CSR activities-the company does not use these funds to make payments to suppliers and employees, interest payments, cash payments, and income tax.…”
Section: Profitability and Social Responsibility Disclosurementioning
confidence: 97%
See 2 more Smart Citations
“…Based on these signals, it can be concluded that the level of CSR disclosure policy will be carried out by the company. In their study, Winarto & Rachmawati (2020) stated that profitability does not affect CSR disclosure. It shows that although the company has a high profit-in other words, it has a lot of money to do CSR activities-the company does not use these funds to make payments to suppliers and employees, interest payments, cash payments, and income tax.…”
Section: Profitability and Social Responsibility Disclosurementioning
confidence: 97%
“…The measurement of leverage in this study uses the Debt to Equity Ratio (DER), a measurement instrument from previous research conducted by Winarto & Rachmawati (2020). The systematic formula is provided below.…”
Section: Leveragementioning
confidence: 99%
See 1 more Smart Citation
“…Environmental cost accounting needs to be reported separately based on the cost classification. This is done so that environmental cost reports can be used as information to evaluate the company's operational performance, especially those that have an impact on the environment (Winarto & Rachmawati, 2020). The allocation of waste costs to products or production processes can provide benefits for the motivation of managers or their subordinates to reduce pollution as a result of the production process.…”
Section: Environmental Cost Accounting Based On a Amanah Metaphor To ...mentioning
confidence: 99%
“…social responsibility is defined as corporate social action that is required by law (McWilliams & Siegel, 2001). The field of corporate social responsibility is currently experiencing rapid growth and is an amalgamation of many theories, approaches, and strategy terminology (Carroll, 1994;Garriga & Mele, 2004;Lepoutre & Heene, 2006;Murdifin et al, 2019;Pramukti et al, 2019;Winarto & Rachmawati, 2020). Shafer (2015) explains that companies must prioritize ethics and responsibility; Even more specifically, Elkington (1997) explains that building a paradigm of corporate governance that emphasizes an inevitability requires a balance between profit, people, and the planet, or better known as the "3P concept".…”
Section: Introduction 12mentioning
confidence: 99%